PALEOGEOGRAPHY: AN EARTH SYSTEMS PERSPECTIVE - Ross G.M. (My University, 1999)
Paleogeography is the subdiscipline within the geosciences that studies the physical and biological geography of the geologic past, including the configuration and latitudinal distribution of continental landmasses, their topographic relief, climate and biota. In recent years, the study of paleogeography has evolved from simple continental reconstructions to more sophisticated paleocontinental maps that form the basis of paleoclimactic modeling by incorporating elements of oceanic and atmospheric circulation and their interactive relationship with landmasses. A broad range of geologic elements can be reconstructed through paleogeographic studies, such as mountain belts, climate zones, emergent land and continental configurations, many of which impact directly on understanding the driving forces behind geochemical signals contained in the rock record which are used as a proxy for biogeochemical processes in Earth history. Paleogeography is thus an essential component of an earth systems approach to interpreting the geologic past. Paleoconfigurations of continents and ocean basins are determined by a variety of techniques. Paleomagnetic studies are the most common, but additional constraints are provided by faunal provincialism (biogeography) and abiotic continental linkages such as pre-break-up magmatism. Recent developments within paleogeography include the use of various forms of climate models to analyze the relationships between global continental reconstructions and the rock record of past climates in order to test more directly feedback between paleogeography and paleoclimate. Development of an extended GIS database for the geological past promises new insights into quantitative analysis of Earth system evolution.
Keywords: PALEOGEOGRAPHY; PALEOMAGNETISM; PALEOCLIMATE; BIOGEOGRAPHY; GEOCHEMISTRY